St. Augustine's Confessions - Cook, William R. (William Robert), 1943-; Herzman, Ronald B.; Teaching Company (Chantilly, VA : Teaching Co., 2004)
An analysis of the classic work Confessions by St. Augustine of Hippo (354-430). Includes Roman history and Christian controversries at the time and background for understanding the book. Also discusses its ongoing usefulness and how it may serve as a guide despite the obvious diffrence between Augustine's world and ours.
part 2. Lecture 13. Book VII, Neo-Platonism and truth -- Lecture 14. Book VII, Faith and reason -- Lecture 15. Book VIII, Converging conversions -- Lecture 16. Book VIII, "Pick it up and read" -- Lecture 17. Book IX, The new man -- Lecture 18. Book IX, The death of Monica -- Lecture 19, Book X, Augustine and the Bishop -- Lecture 20, Book X, Augustine on memory -- Lecture 21. Book XI, Augustine on time -- Lecture 22. Book XII, Augustine on biblical interpretation -- Lecture 23. Book XIII, Augustine on creation -- Lecture 24. The Confessions through the ages.
24 Lectures.
Lecturers, William R. Cook, Ronald B. Herzman.
"Course no. 6627."
Compact disc.
Accompanying course guidebook includes a glossary, biographical notes, and a bibliography.
Instructed by William R. Cook and Ronald B. Herzman.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Catholic Church -- Bishops -- Biography -- Early works to 1800.; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography; Audiobooks